(untitled) (Nuntius Antiquus, 2013)
This text presents a free verse translation of the prologue (1-41) to The Suppliants, by Euripides. It is followed by a panoramic introduction highlighting the religious background that underpins this tragedy in order to better set the context in which Aethra enters onto the stage.